HBeAg and Anti HBe Status in Patients with Chronic Hepatitis B Infection - Haris Widita; Stephanus Gunawan; Baskoro Tri Laksono; Wenny Astuti Achwan; I Gusti Putu Wilusanta; Ketut Mahendra; Herman S Taufiq; Soewignjo Soemohardjo (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2010)
Background: Data on HBeAg and anti HBe status in patients with chronic hepatitis B infection are not yet available in Indonesia. This study was done to acquire data on HBeAg and anti HBe status in patients with hepatitis B chronic infection. Method: The material of this study was sera, collected from 105 patients with chronic hepatitis B infection from June to November 2007, divided into four groups of hepatoma, liver cirrhosis, chronic hepatitis B and asymptomatic HBsAg carriers. All sera were examined for HBsAg, HbeAg, anti HBe aside from liver function examinations. The sera consisted of 23 sera of patients with hepatoma, 27 with liver cirrhosis, 12 with chronic hepatitis B, and 43 with HBsAg asymptomatic carriers. Results: From 105 samples, only 18.1% samples were in replicative phase, as shown with the positivity of HBeAg and the negativity of anti-HBe. Sera with negative HbeAg and positive anti-HBe were mainly found in liver cirrhosis (70.73%) and least in chronic hepatitis B (50.00%) Conclusion: The high frequency of HBeAg negative and anti-HBe positive in this study might indicate the possible high frequency of pre core mutation. A study using quantitative HBV DNA should be done to confirm it.   Keywords: HBeAg, anti HBe, chronic hepatitis B